Manufacture of Struvite From Industrial Waste Sodium Tripolyphosphate Using Bulkhead Column Reactor - Sutiyono; Luluk Edahwati; Adeniah Setiabudi; Suhaili (Nusantara Science and Technology Proceedings, 2022)
The utilization of Industrial Waste Sodium Trypolyphosphate to be used as struvite fertilizer is still very few. Sodium Trypolyphosphate Industrial Waste has a very high phosphate content, which is 21610 mg/l. Struvite is one type of inorganic fertilizer, where this fertilizer is a slow-release fertilizer. This fertilizer is known as Magnesium, Ammonium, Phosphate. The main objective of this study was to determine the best temperature and molar ratio in the formation and quality of the struvite produced. In this study, uses a device in the form of a Bulkhead Column Reactor, with the help of air as a stirrer. The process with the Bulk Column Reactor is carried out using several variables, namely the temperature variable and the molar ratio variable. The temperature used is 30oC. As for the molar ratio, it is, 1:1:1; 2:1:1 and 3:1:1. The best results from this study were at a temperature of 30oC with a molar ratio of 3 : 1: 1, where the struvite produced had a magnesium content of 3.8% and a phosphate content of 33.8%.